(3eXgQ GdJHLjd dbhd MSHi Gddg hfYe Gdhcjds - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjb SejJg eXgQ GdJHLjd dbhd MSHi Gddg hfYe Gdhcjd HbQCJi Ydjg s
(3BNQgG (B:s
(3hddMGaX CHj TGeI ai eMfJg bdJ Cf bGd EdG fTJci , eG bO LQi agh NWH Wjc , jbHV Gddg JYGdi dfG , ef jCNP GdMb hjTai GdZdjd , EPG JhcdfG Ydjg caG aMSHfG Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJUha hGdBOGH GdTQYjIs